1990
DOI: 10.1063/1.458116
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of molecular dissociation through an electronic curve crossing: Polarized emission spectroscopy of CH3I at 266 nm

Abstract: We present a study of the dissociation of CH3I on coupled repulsive electronic potential energy surfaces by the technique of polarized emission spectroscopy. We excite CH3I at 266 nm and disperse the photons emitted from the dissociating molecule by both frequency and angular distribution with respect to the polarization direction of the excitation laser. We thus measure the polarization of the first 12 C–I stretching emission features, corresponding to the spectral region between 266 and 317 nm. We also obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(83 citation statements)
references
References 58 publications
9
74
0
Order By: Relevance
“…2͑c͒ at an incident energy of 30 eV and 20°scattering angle, where the 1 Q 1 perpendicular transition becomes more prominent. This is also reinforced by the polarized emission spectroscopy of Lao et al 29 at 4.66 eV ͑266 nm͒, who reported a gradual increase in emission from the 1 Q 1 potential energy surface on the n 3 overtones. This is also in agreement with the recent reported resonant feature of CH 3 I at 4.7 eV, in the vibrational excitation DCS of Kato et al 2 Nevertheless, Strobel et al 14 have indicated an increasing relevance of the coupling with a longer evolution time of the wave packet on the potential energy surface.…”
Section: -3supporting
confidence: 52%
“…2͑c͒ at an incident energy of 30 eV and 20°scattering angle, where the 1 Q 1 perpendicular transition becomes more prominent. This is also reinforced by the polarized emission spectroscopy of Lao et al 29 at 4.66 eV ͑266 nm͒, who reported a gradual increase in emission from the 1 Q 1 potential energy surface on the n 3 overtones. This is also in agreement with the recent reported resonant feature of CH 3 I at 4.7 eV, in the vibrational excitation DCS of Kato et al 2 Nevertheless, Strobel et al 14 have indicated an increasing relevance of the coupling with a longer evolution time of the wave packet on the potential energy surface.…”
Section: -3supporting
confidence: 52%
“…Hence the problem is simplified to the extent of finding the velocity at the crossing point. For this the translational energy (E,) at the asymptotic limits is calculated using a quasidiatomic model and is given by Can parameter, as pointed out by Lao et al (14). However, a detailed model to describe the dynamics will be complicated and c o nputationally demanding.…”
Section: Discussionmentioning
confidence: 99%
“…This spec-CH 3 trum was qualitatively consistent with a picture of the initial photodissociation dynamics involving almost pure stretching of the CÈI bond and Ñattening of the dihedral angle at later times. The polarization CH 3 properties of the resonance Raman scattering of iodomethane have also been examined by both Lao et al 50 and more recently Wang and Ziegler51 in order to quantitate the contributions from electronic states other than Resonance Raman spectra of iodomethane 3Q 0 . have been obtained in several solvents to examine environmental e †ects on the early time photodissociation dynamics by Myers and Markel.52h54 Resonance Raman spectra have also been obtained for both vapour-and solution-phase iodoethane, 2-iodopropane and tert-butyl iodide.55h57 The solutionphase study56 reported both relative and absolute resonance Raman cross-sections over a wide range of excitation wavelengths and showed that the vibrational fundamentals in the A-band resonant Raman spectra derive much of their intensity from higher electronic states.…”
Section: Introductionmentioning
confidence: 98%